The chemical limnology of Lake Bonney, Antarctica, with emphasis on trace metals and nutrients - Weand, Barron L. (Virginia Polytechnic Institute and State University, 1975)
Chemical parameters of Lake Bonney, southern Victoria Land, Antarctica, were closely monitored during the 1973-74 and 1974-75 austral summers using marine analytical techniques and the method of standard additions. Results were at variance with reports of several previous investigators. Inorganic nitrogen was found to be present in high concentrations, particularly in the monimolimnion, and the dominant inorganic species was generally ammonia. Orthophosphate-phosphorus concentrations in the mixolimnion were ordinarily less than 10 g/l throughout the study. Water samples were analyzed for the presence of copper, cobalt, iron, manganese, molybdenum, and nickel using flameless atomic absorption. More than 90 percent of the mass of each trace metal was found to be in the monimolimnion. Manganese was by far the most abundant trace metal in the lake, and some evidence suggests it may present a toxicity problem to algae in the surface waters. Concentrations of copper potentially toxic to at least algal species in the lake were present in the monimolimnion and, at times, in the mixolimnion. Continuous monitoring of one meltstream showed flows to be highly variable. Most of the orthophosphate-phosphorus carried to the lake by this meltstream was transported during the first two weeks of flow, probably due to the leaching of phosphates from the products of weathering generated over the long Antarctic winter. Whereas the meltstreams were previously considered as potential sources of significant quantities of nitrogen and phosphorus, it was determined that they probably contribute relatively minor amounts of these nutrients. The loading of trace metals to the lake also appears to be of minor importance, with the possible exception of cobalt. A decided peak in sulfate concentration and concomitant drop in pH was observed during each field season. Because no precursor to the sulfate could be identified, the mechanism for this phenomenon is not apparent, but may be related to subterranean inflow. The hypothesis that there is ...